Handwritten tifinagh character recognition using simple geometric shapes and graphs - Youssef Ouadid; Abderrahmane Elbalaoui; Mehdi Boutaounte; Mohamed Fakir; Brahim Minaoui (Institute of Advanced Engineering and Science, 2019)
In this paper, a graph based handwritten Tifinagh character recognition system is presented. In preprocessing Zhang Suen algorithm is enhanced. In features extraction, a novel key point extraction algorithm is presented. Images are then represented by adjacency matrices defining graphs where nodes represent feature points extracted by a novel algorithm. These graphs are classified using a graph matching method. Experimental results are obtained using two databases to test the effectiveness. The system shows good results in terms of recognition rate.